(untitled) (NAU Journal of Technology and Vocational Education, 2024)
This study determinedthe effect of Student-Led Seminars (SLS) on academic achievement in Financial Accounting among secondary school students in Abia State. Two research questions guided the study and three null hypotheses were tested. Quasi- experimental research design specifically; pre-test, post-test non-equivalent control group design was adopted for the study. Population comprised the entire 1,098 students offering Financial Accounting in public secondary schools in Abia state. A purposive sampling technique was used to draw a sample of 100 SS1 Financial Accounting students. Financial Accounting Achievement Test (FAAT) was used for data collection. The face and content validity of the instrument were established using three experts, while Kudder-Richardson Formula 20 (KR-20) was used to establish the reliability of coefficient of 0.98. Mean and standard deviation were used to answer the research questions while Analysis of Covariance (ANCOVA) was used to test the null hypotheses. Findings of the study revealed among others that SLS is more effective in enhancing students’ academic achievement in Financial Accounting thanthe conventional teaching methods (CTM); which also enhanced academic achievement ability of female students than males in Financial Accounting. It was, therefore, recommended among others that Financial Accounting teachers should use more of SLS in teaching the subject to facilitate better understanding and performance of students.